2021
DOI: 10.1002/ccr3.3885
|View full text |Cite
|
Sign up to set email alerts
|

Mucopolysaccharidosis (MPS): Review of the literature and case series of five pediatric dental patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 9 publications
0
16
0
1
Order By: Relevance
“…However, a lot of its cases are passed on in an autosomal recessive patern, with only type II passed on in an X-linked pattern. 15 The mucopolysaccharidoses are inbred metabolic disturbances noted to provide clinical matter, mainly corresponded to airway, cardiac and skeletal anomaly, in children in the course of anesthesia. The alteration clinical superintendence of the mucopolysaccharidosis can be explained in three stages.…”
Section: Anesthetic Involvement Of the Alteration Superintendence Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, a lot of its cases are passed on in an autosomal recessive patern, with only type II passed on in an X-linked pattern. 15 The mucopolysaccharidoses are inbred metabolic disturbances noted to provide clinical matter, mainly corresponded to airway, cardiac and skeletal anomaly, in children in the course of anesthesia. The alteration clinical superintendence of the mucopolysaccharidosis can be explained in three stages.…”
Section: Anesthetic Involvement Of the Alteration Superintendence Of ...mentioning
confidence: 99%
“…Atracurium, a muscle relaxant, if used for a long time, can cause delayed offset in patients. 15 As recommended, administration of glucose supplements, frequent perioperative blood sugar monitoring, and neuromuscular blockade are recommendations to this group of patients. No specific approach to anesthesia would be recommended.…”
Section: Children With Medium-chain Acetyl-coa Dehydrogenase Deficiencymentioning
confidence: 99%
“…DTE is the most encountered deviation from normal eruption. 68 Gaucher disease, glycogen storage disorder types 1a and 1b, I-cell disease (mucolipidosis II), mucopolysaccharidoses (predominantly Hurler Scheie, Hunter and Maroteaux Lamy syndrome) 25,69 portray systemic conditions with a predilection for DTE. Moreover, local factors such as cleft lip and palate, bony pathology, and supernumerary teeth that occur as part of certain IEM have a possibility to cause a localised DTE.…”
Section: Considerations In the Dental Management Of Metabolic Disordersmentioning
confidence: 99%
“…Taurodontism describes a dental anomaly which results in enlargement of the pulp chamber vertically at the T A B L E 1 Dental features commonly found in constituent inherited metabolic disease. 4,5,7,17,25,43,51,52,58,62,66,69,[76][77][78][79][80][81][82] expense of the roots and can be seen in glycogen storage disorders (GSD), various mucopolysaccharidosis and multiple sulfatase deficiency. A cross sectional study of 14 MPS patients (mixed diagnoses) showed taurodontism in 57%, 22 whereas taurodontism in GSD is limited to single case reports and case series.…”
Section: Dental Anomaliesmentioning
confidence: 99%
“…Стоматологические проблемы. Часто упускаемыми симптомами из-за проблем в поведении становятся случайные стоматологические находки, такие как облитерированные камеры пульпы и корневые каналы, гипоплазия дентина [25,26].…”
Section: таблица классификация подтипов мукополисахаридоза III типаunclassified